Inverse perovskite solar cell stability using MoS2 (2018)
The present thesis studies the fabrication and stability of organic-inorganic CH3NH3PbI3 solar cells. Due to their high reported efficiency and easy processability, photo-voltaics are being reinvented with perovskite technology. PVK's are fast producing, low cost, rapidly increasing efficiency technology. Their stability development could make photo-voltaics a viable alternative for energy production. By using a layer of MoS2, the perovskite is protected from moisture and ion migration from in the environment and the metal electrode. Using inverse architecture, the MoS2 is placed over the ETL layer (PCBM). This proved to be an effective treatment to conserve short circuit current (Isc) and maintained the shape of I-V curves, while non protected devices lost all their characteristics.